A physiological and kinematic comparison of two different lean back positions during stationary rowing on a Concept II Machine - Bell, G.; Bennett, J.; Reynolds, W.; Syrotuik, D.; Gervais, P. (Journal of Human Kinetics, 2013)
This study compared two different body positions at the finish of a stroke during stationary rowing exercise on physiological and kinematic measurements. Nine male and five female rowers volunteered for the study: mean age (± SD), body height and body mass were 27 ±9 yrs, 180.5 ±12.3 cm and 81.2 ±14.2 kg. The two body positions at the finish were controlled at an upright posture or a novel greater lean back position. All subjects completed 3 different experimental trials on a Concept IID rowing machine at 3 different exercise intensities and comparisons were made between the lean back position at the same stroke rate and the same power output as the upright trial. Power output, heart rate, oxygen uptake, energy expenditure and % efficiency were higher (p<0.05) with the greater lean back position at the same stroke rate compared to all other conditions. Range of motion at the hip, ankle, and elbow and the handle velocity and distance moved were greater (p<0.05) with the lean back position. In conclusion, a greater lean back posture at the finish during stationary rowing produces a higher power output and improved efficiency at the same stroke rate but at an elevated physiological cost compared to a more upright position. Despite the higher energy expenditure, the relative gain in power output and efficiency with no negative kinematic changes suggests that a greater lean back position at the finish will enhance performance during stationary rowing exercise.